Pengaruh Konsentrasi Injeksi Antemortem Larutan Getah Pepaya (Carica Papaya, L.) Secara Intra Muskular Terhadap Keempukan Daging Bebek (Anas Platyrhynchos) Petelur Afkir Mojosari - Puspa Ramadhani (2015)
This study attemps to prove that papaya latex affected to the rejected duck meat tenderness. This study used Completely Randomized Design (CRD) Tukey’s test for raw and boiled meat, and Kruskal-Wallis test for organoleptic with 24 rejected ducks as experimental animals and continued by Honesty Significant Different (HSD). The ducks were divided into six treatment groups: P0 (injected by 10 ml aquadest), P1 (injected with 1% papaya latex solution). P2 (injected with 2% papaya latex solution), P3 (injected with 4% papaya latex solution), P4 (injected with 8% papaya latex solution), P5 (injected with 16% papaya latex solution) and four replications. Each treatment group had a same age, weight, and was fed by the same feed. The findings of this study indicated papaya latex solution significantly improved the tenderness of the rejected duck meats (p<0,05). Tenderness (raw meat) of P1 and P2 had the highest mean (202,00 and 205,00) and significantly different from P0, P3, P4, and P5. Tenderness (boiled meat) of P2 and P3 P2 were the highest (315,00 and 404,00) and significantly different from each other and P0, P1, P4, and P5. Tenderness (organoleptic) of P4 was the highest (98,92) and significantly different with P0, P1, P2, and P3. The results of rejected duck examination indicated that papaya latex provide significant effect on meat tenderness (p<0,05).